Implementation of Religious Moderation Value in Al-Azhar Superior High School, Medan Johor Sub-District - Tansri Riziq Hilman Afif; Farhan Hidayat; Alwanda Putra; Liza Wardani; Meyniar Albina (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to explore the implementation of religious moderation values at SMA Unggulan Al-Azhar Medan Johor, focusing on four main indicators: national commitment, tolerance, non-violence, and acceptance of local traditions. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation studies. The results showed that SMA Unggulan Al-Azhar Medan Johor has successfully integrated the values of religious moderation in various aspects of education, including the curriculum, extracurricular activities, and students' daily lives. This implementation includes strengthening the sense of nationalism through activities such as flag ceremonies and extracurricular nationalism; instilling tolerance through inclusive religious learning and cultural arts activities; establishing a safe environment free of violence through the Anti-Bullying Task Force program; and respect for local traditions through arts and cultural activities. In conclusion, SMA Unggulan Al-Azhar Medan Johor has succeeded in creating an educational environment that is tolerant, harmonious, and appreciates diversity, while forming a young generation that is moderate, inclusive, and loves the country. This research contributes to the development of a religious moderation-based education model that is relevant to the challenges of the times.